ABOUT THE CATEGORY OF IMPLICITNESS (Scientific journal of the Fergana State University, 2026)
The article discusses the category of implicitness. The implicit - a terminological system with a hidden meaning - is subjected to analysis. Also, the paradigmatic system of the category of implicitness is explained through a review of theoretical literature.